ANALISA PENGARUH INVESTASI DAN GDP RIIL TERHADAP PEMAKAIAN KONSUMSI ENERGI LISTRIK - Dyah Wahyu Ermawati; David Kaluge (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2005)
The objective of this research is to analyze the impact of real GDP (Gross Domestic Product) and investment on the consumption of electricity energy in the ASEAN countries (Malaysia, Phillippine and Indonesia). From the result of the analysis, it is found that there are significant influences of the real GDP and investment on the consumption of the electricity energy. Partially, real GDP and investment doesn’t have any significant influence on the consumption of electricity for Malaysia and Indonesia. Estimation model show that an increasing trend of consumption of electricity, investment and real GDP.